Pilotprojekt Gropiusstadt : Jahrbuch 2003. (Berlin : Kulturnetzwerk Neukölln Berlin, 2003)
Bosch, Susanne ; Eggers, Carsten ; Fadmi, Mimi ; Familie Bleser ; Fox, Bernd ; Grüss, Heike ; Haenlein, Karin Missy Paule ; Hara, Takafumi ; Hasucha, Christian ; Heise, Juliane ; Vaara, Roi ; Janik, Iga ; Kirsch, R.J. ; Koselleck, Ruppe ; Kurzwelly, Michael ; Monochrome Circus ; de Munk, Leo ; Porst, Anne ; Potter, Naomi ; Rizzi, Mario ; Schumacher & Jonas ; Seipel, Spunk ; Siegfried, Walter ; Silver, Daniel
zie kast losse tijdschriften
Duits
boek